Etnozoologi dan karakteristik walabi (Dorcopsis muelleri) satwa endemik New Guinea di Kabupaten Sorong Selatan - Dwiranti, Febriza; Rumalean, Fitriani; Krey, Keliopas (Cassowary, 2026)
Dorcopsis muelleri is a marsupial that is endemic to New Guinea. This research is designed to describe local wisdom on ethnozoology and characteristic Dorcopsis muelleri, wallaby in South Sorong district. This is descriptive research, and data were collected using a field survey with semi-structured interviews based on questionnaires to mammal hunters. Research variables are the identity of respondents, knowledge of D. muelleri, morphological characteristics, hunting activity and functions or daily use of Wallaby by the local communities. The results indicate that majority local community’s hunters in South Sorong districts are originally from local people (92,3%) and Timor ethnics (7,7%), ages from 30-40 years (53,8%), and 84,6% hunters finished higher school education level, which has important roles to preservation and inheritance local wisdoms for ethnozoology, but the majority of the hunters did not know endemic status of D. muelleri to New Guinea. Wallaby hunting by local people in South Sorong usually uses various traditional methods, such as dog help, snares or traps made from local materials, and air rifles. Wallaby meat is served and consumed after being burned on fire, and local recipes and ingredients are used, which reflects the local wisdom in maintaining their surrounding ecosystem. This hunting activity is conducted to earn money by selling the hunting meat and to fulfill animal protein and needs from local resources. In Indonesian, D. muelleri is called Wallaby biasa hutan or Dorcopsis coklat because it has brown feathers, rough fur, and a tail that is 1/5 of the whole tail.